2013
DOI: 10.2217/epi.13.68
|View full text |Cite
|
Sign up to set email alerts
|

Epigenomics and Allergic Disease

Abstract: Allergic disease development is affected by both genes and the environment, and epigenetic mechanisms are hypothesized to mediate these environmental effects. In this article, we discuss the link between the environment, DNA methylation and allergic disease, as well as questions of causality inherent to analyses of DNA methylation. From the practical side, we describe characteristics of allergic phenotypes and contrast different epidemiologic study designs used in epigenetic research. We examine methodological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 154 publications
(166 reference statements)
0
20
0
2
Order By: Relevance
“…Epigenetic modifications contain histone modification, noncoding RNAs, chromatin remodeling, and DNA methylation. DNA methylation is one of the most common epigenetic modifications in eukaryotic cells and its functions in allergic diseases have been enthusiastically debated in recent years 1617. Forkhead box p3 ( Foxp3 ) is the specific transcription factor of CD4 + CD25 + Treg cells and is a critical regulator of their development and function 1819.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic modifications contain histone modification, noncoding RNAs, chromatin remodeling, and DNA methylation. DNA methylation is one of the most common epigenetic modifications in eukaryotic cells and its functions in allergic diseases have been enthusiastically debated in recent years 1617. Forkhead box p3 ( Foxp3 ) is the specific transcription factor of CD4 + CD25 + Treg cells and is a critical regulator of their development and function 1819.…”
Section: Introductionmentioning
confidence: 99%
“…No obstante, las reacciones a medicamentos severas (como SJS y TEN), que pueden ser evitadas aproximadamente en un 80%, se han visto relacionadas en el caso de tener el HLA-B*5701 e iniciar tratamiento con el abacavir (inhibidor de la transcriptasa reversa de tipo nucleótido usado en el virus de la inmunodeficiencia humana), por lo que este es un ejemplo de un examen rutinario usado ampliamente en la práctica clínica de los países desarrollados (58)(59)(60). Es por esto, que se habla de la epigenética, es decir cómo influyen los factores ambientales en la expresión de ciertos genes (2,11). En la tabla 3 se dan ejemplos de los genes relacionados con algunas enfermedades alérgicas (61-68) y en la tabla 4 los estudios de HLA en hipersensibilidad a medicamentos (69)(70)(71)(72)(73)(74)(75).…”
Section: Genéticaunclassified
“…En ésta, influyen principalmente factores genéticos y ambientales. El primer factor se considera el más importante por sí solo (2), al decirse que si un progenitor es alérgico, el riesgo de que su hijo lo sea es del 30%, si ambos padres lo son, se habla del 50%; y si son gemelos idénticos la probabilidad es de un 70% (1). En cuanto al segundo factor, las principales fuentes de alérgenos son: 1-) Alimentos como mariscos, soja, trigo, maní, leche, huevos, siendo estos tres últimos los que más comúnmente generan reacciones alérgicas (3,4), 2-) Medicamentos, entre los que están: β-lactámicos, ácido acetilsalicílico (ASA), trimetoprim-sulfametoxazol, vancomicina, antiinflamatorios no esteroideos (AINES), 3-) Animales, como reptiles e insectos y 4-) Otros como látex, vacunas, medios de contraste radiológicos y polen (5).…”
unclassified
“…DNA-M, the addition of a methyl group to a cytosine followed by a guanine (CpG sites, CpGs), is known to mediate the effect of environment at transcriptional levels, and also has well-evidenced connections to allergic disease [13]. An immunological study suggested that epigenetic changes in vaccine-induced memory CD4 and/or CD8 T cells act as on-off-on switches for immune responses after re-exposure to antigen [4].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that DNA–M may modulate the regulation of genes that are associated in the pathogenesis of asthma and allergy [13,1619]. …”
Section: Introductionmentioning
confidence: 99%